2013
DOI: 10.1107/s2052519213023087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lone-pair stereoactivity on polyhedral volume and structural flexibility: application to TeIVO6octahedra

Abstract: The Distortion Theorem implies that the irregularity of bond distances in a distorted coordination polyhedron causes an increase of mean bond distance. Examination of 40 polyhedra containing the lone-pair cation Te(IV) shows that this does not imply an increase in polyhedral volume. Volumes of these polyhedra are 10.3-23.7 Å(3), compared with the 12.83 Å(3) expected for a hypothetical regular octahedron. There is little correlation between volume and measures of polyhedral distortion such as quadratic elongati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 71 publications
2
24
0
Order By: Relevance
“…When it occurs, stereoactivity usually causes strong distortion of the Te 4+ O 6 polyhedra (cf. Christy and Mills, 2013). Ordering of Te 4+ and Te 6+ in the octahedral sites is the cause of the symmetry reduction from cubic.…”
Section: +mentioning
confidence: 99%
“…When it occurs, stereoactivity usually causes strong distortion of the Te 4+ O 6 polyhedra (cf. Christy and Mills, 2013). Ordering of Te 4+ and Te 6+ in the octahedral sites is the cause of the symmetry reduction from cubic.…”
Section: +mentioning
confidence: 99%
“…Mills et al, 2012), and more recently for helping advance the knowledge of the crystal chemistry of tellurium (e.g. Mills and Christy, 2013;Christy and Mills, 2013;Christy et al, 2016). Andy Christy has agreed to the naming of this mineral in his honour.…”
Section: Introductionmentioning
confidence: 99%
“…, as it possesses a stereoactive lone pair of electrons, which causes strong asymmetry in its coordination shell, with a very wide range of Te-O bond distances and bond valences Christy and Mills, 2013). Thus, it is necessary to define a bond-valence cut-off beyond which Te-O links cease to be part of the FBB.…”
Section: +mentioning
confidence: 99%
“…As part of a broader study of tellurium mineralogy, we have reinvestigated the stereochemistry of Te Christy and Mills, 2013), and undertaken a comprehensive review of the structural diversity of Te oxysalt compounds (Christy et al, 2016). While undertaking the review, we discovered that many Te compounds have reoccurring structural motifs (Christy et al, 2016) such as the Cu 2 Te ribbon found in frankhawthorneite , timroseite (Kampf et al, 2010e), paratimroseite (Kampf et al, 2010e) and bairdite (Kampf et al, 2013c), which suggested that Te oxysalt mineral structures form a structural hierarchy that might also correlate with paragenetic order, as do those noted above for other chemical classes of mineral.…”
Section: Introductionmentioning
confidence: 99%